Partnerstwo rodziny i szkoły dla rozwoju cnót - Bernasiewicz , Maciej; Gierczyk , Marcin (Studia Edukacyjne, 2019)
Many types of research appear to show that communication barriers and a bad relationship between teachers and parents can hinder the development of behavioral skills and cognitive capacities that enable some individuals to put their moral habits into their life. Teachers’ and parents’ common aim is to create in young people attitudes consistent with the given system of values. This article is a theoretical overview of the issues related to the family-school partnership about Virtue Development, on the basis of which the authors proposed a conceptual model of an interdependent and interrelated relationship between teachers and parents and demonstrated how the inclusion of parents, students and teachers in broadly understood activities for the benefit of others (people, animals, nature, etc.) is particularly valuable from the point of view of moral development in Polish schools.